Pengembangan Strategi Literasi Keluarga Untuk Meningkatkan Minat Baca Anak Usia Dini (Penelitian Pengembangan pada siswa kelompok B PAUD BAI Rumah Cendekia Kabupaten Bogor) - Nurdini Ferianti; Irna Irna (Cetta: Jurnal Ilmu Pendidikan, 2020)
This research has a purpose to increase the reading interest of childhood through literacy activities based on family. In fact, reading interest of childhood is still low. It’s caused by low motivation of child in reading. The low stimulation of reading can obstruct development of chid language. One of strategies that can implemented to increase this reading interest in this research is Literacy activities based on family. This family literacy activities is given to children in their family. Research methode that’s used in this research is Research and Development. This research consist of introduction, litercy strategic development based on family, validation of literacy strategies based on family, trials and revision of literacy strategies development based on family and the last is implementation of procedure of literacy sstrategies development based on family. Subyek of this research are students of class B in PAUD BAI Rumah Cendekia, in Bogor Disstrict. Result of this research is hoped can become on of alternatives of strategies in increasing the reading interest of childhood